Epithelial IL-6 trans-signaling defines a new asthma phenotype with increased airway inflammation - Jevnikar, Zala; Östling, Jörgen; Ax, Elisabeth; Calvén, Jenny; Thörn, Kristofer; Israelsson, Elisabeth; Öberg, Lisa; Singhania, Akul; Lau, Laurie C.K.; Wilson, Susan J.; Ward, Jonathan A.; Chauhan, Anoop; et al. (Elsevier, 2018)
Background: Although several studies link high levels of IL-6 and soluble IL-6 receptor (sIL-6R) with asthma severity and decreased lung function, the role of IL-6 trans-signaling (IL-6TS) in asthma is unclear. Objective: To explore the association between epithelial IL-6TS pathway activation and molecular and clinical phenotypes in asthma. Methods: An IL-6TS gene signature, obtained from air-liquid interface (ALI) cultures of human bronchial epithelial cells stimulated with IL-6 and sIL-6R, was used to stratify lung epithelium transcriptomic data (U-BIOPRED cohorts) by hierarchical clustering. IL-6TS-specific protein markers were used to stratify sputum biomarker data (Wessex cohort). Molecular phenotyping was based on transcriptional profiling of epithelial brushings, pathway analysis and immunohistochemical analysis of bronchial biopsies. Results: Activation of IL-6TS in ALI cultures reduced epithelial integrity and induced a specific gene signature enriched in genes associated with airway remodeling. The IL-6TS signature identified a subset of IL-6TS. High asthma patients with increased epithelial expression of IL-6TS inducible genes in absence of systemic inflammation. The IL-6TS High subset had an overrepresentation of frequent exacerbators, blood eosinophilia, and submucosal infiltration of T cells and macrophages. In bronchial brushings, TLR pathway genes were up-regulated while the expression of tight junction genes was reduced. Sputum sIL-6R and IL-6 levels correlated with sputum markers of remodeling and innate immune activation, in particular YKL-40, MMP3, MIP-1β, IL-8 and IL-1β. Conclusions: Local lung epithelial IL-6TS activation in absence of type 2 airway inflammation defines a novel subset of asthmatics and may drive airway inflammation and epithelial dysfunction in these patients.